Associations of Tea Consumption With the Risk of All‐Cause and Cause‐Specific Mortality Among Adults With Type 2 Diabetes: A Prospective Cohort Study in China - Lifeng Wang; Xikang Fan; Jian Su; Yu Qin; Zhongming Sun; Yan Lu; Shujun Gu; Chong Shen; Jinyi Zhou; Hao Yu; Ming Wu (Journal of Diabetes)
ABSTRACT Aims To investigate the associations of tea consumption with all‐cause and cause‐specific mortality among type 2 diabetes mellitus (T2DM) Chinese patients. Materials and Methods The present study included 15 718 participants from the Comprehensive Research on the Prevention and Control of Diabetes between 2013 and 2014 in Jiangsu, China. Information on tea consumption (including frequency, amount, and duration) was collected at baseline using interviewer‐administered questionnaires. Death data were identified by linkage to the Death Certificate System. Cox proportional hazard regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results During a median follow‐up of 9.77 (9.69, 9.82) years, 3046 deaths were documented, including 922 from cardiovascular disease (CVD) and 736 from cancer. Compared with nonconsumers, regular tea consumption (≥ 3 times/week, 1 cup/day, > 30 years) was associated with reduced all‐cause mortality risk in T2DM, with HRs (95% CIs) of 0.82 (0.74, 0.91), 0.80 (0.72, 0.89), and 0.77 (0.68, 0.86). For cardiovascular mortality, the HRs (95% CIs) were 0.79 (0.65, 0.96), 0.72 (0.59, 0.89), and 0.75 (0.60, 0.93). The exposure‐response relationship suggested that consuming 4 g/day may offer the most evident health benefits. Conclusions Among Chinese T2DM patients, higher tea frequency and amount intake were associated with lower risk of all‐cause and CVD mortality. It is suggested that consuming 4 g/day of tea could potentially serve as an intervention target. These findings suggest that tea consumption can be a part of a healthy diet for T2DM patients.